Incorporating social and sustainability aspects into econometrics of agroforestry: a case from South India - Babu, Suresh Chandra; Shanmugam, T. (2004)
In spite of the well known economic, social, and sustainability benefits of agroforestry systems, the adoption of agroforestry technologies continues to be very slow in developing countries. This is partly due to the design and implementation of agroforestry expansion programs, which rely heavily on the economic benefits and costs of agroforestry technologies, while the social and sustainability benefits remain unaccounted for. This paper is an attempt to incorporate social and sustainability benefits into the evaluation of agroforestry systems. Based on a case study of 200 farmers engaged in four types of agroforestry systems in the south Indian state of Tamil Nadu, it shows that if the externalities associated with agroforestry were internalized, these systems would be more attractive as investments. The paper argues that the future evaluation of agroforestry systems should account for both private and societal benefits.